Zdůvodnění a přínos hodnotové anamnézy v klinické praxi: postoj pedagogů vnitřního lékařství - Rusinová, Kateřina; Sládková, Tereza; Vrablík, Michal; Židková, Alexandra; Petrů, Tereza; Dušek, Pavel; Matějovič, Martin (Vnitřní lékařství, 2023)
Aim: In patients with severe illnesses, particularly in situations of unfavorable prognosis, it is essential to consider and decide on the appropriateness of further treatment. The ability to conduct a values-oriented conversation is crucial for providing care that aligns with the patient's values and preferences. Values History Taking (VHT) should be included in the curriculum of medical schools. Method: A questionnaire survey mapping the attitudes of internal medicine educators at the 1st Faculty of Medicine, Charles University, and the Faculty of Medicine in Plzeň, Charles University, regarding the significance, experiences, potential benefits, and barriers of incorporating value history taking into the teaching of standard medical history interviews. Results: A total of 123 questionnaires were evaluated in the study. Currently, value history taking, as well as its individual elements, are not widely integrated into medical education or practice. However, most physicians (83%) consider it very important. Among the potential benefits, they see higher patient and family satisfaction, greater ability to respect the patient's wishes, and the potential reduction in the number of unplanned or unwanted rehospitalizations towards the end of life. Conclusion: The positive attitude of educators supports the need for the integration of value history taking into both education and routine clinical practice. Value history taking becomes a part of the structured medical history interview in the subject of Internal Propaedeutics and Internal Medicine at the 1st Faculty of Medicine, Charles University, and the Faculty of Medicine in Plzeň, Charles University.
Keywords: Education, Medical; Medical History Taking; Advance Directives; komunikace; Physician-Patient Relations; anamnéza; lidé; pacientova přání ohledně budoucí terapie; průzkumy a dotazníky; Palliative Care; vztahy mezi lékařem a pacientem; studium lékařství; Surveys and Questionnaires; paliativní péče; Communication; Humans